2016
DOI: 10.1371/journal.pone.0148145
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Divergence in Feed Efficiency on the Intestinal Microbiota and the Intestinal Immune Response in Both Unchallenged and Lipopolysaccharide Challenged Ileal and Colonic Explants

Abstract: Feed efficiency is an important trait in pig production, with evidence to suggest that the efficiencies of a variety of biological systems contribute to variation in this trait. Little work has been conducted on the contribution of the intestinal innate immune response to divergence in feed efficiency. Hence, the objective of this study was to examine select bacterial populations and gene expression profiles of a range of targets relating to gut health and immunity in the intestine of pigs phenotypically diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
57
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 32 publications
12
57
0
Order By: Relevance
“…However, this study is one of the first to exploit this technology to examine the intestinal microbiota among pigs of varying FE. The metric used for FE was RFI, and ranking pigs according to this measure was particularly useful, as it allowed the selection of pigs that consume less feed to achieve the same weight gain, in agreement with previous findings for pigs divergent in RFI (14,31). To minimize the variability in FE due to external factors, pigs were ranked by RFI within litter (to control for genetic influences), and all pigs were subjected to the same management, environmental, and nutritional conditions.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…However, this study is one of the first to exploit this technology to examine the intestinal microbiota among pigs of varying FE. The metric used for FE was RFI, and ranking pigs according to this measure was particularly useful, as it allowed the selection of pigs that consume less feed to achieve the same weight gain, in agreement with previous findings for pigs divergent in RFI (14,31). To minimize the variability in FE due to external factors, pigs were ranked by RFI within litter (to control for genetic influences), and all pigs were subjected to the same management, environmental, and nutritional conditions.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, bacterial diversity within the intestinal tract was found to be higher in pigs with heavier body weights and improved growth rates (3,21). However, to our knowledge, only one study to date has investigated the association between FE in pigs and the intestinal microbiota (14). It demonstrated an increased abundance of Lactobacillus in the cecum of more feed-efficient pigs; however, only Firmicutes, Bacteroidetes, Bacteroides, Lactobacillus, and Enterobacteriaceae were measured (by quantitative PCR).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies reported an enhanced ileal digestibility of energy and expression of SGLT1 and GLUT2 in the jejunum of growing pigs [3,14], whereas other did not find RFI-related differences for digestive efficiency [2,12]. Likewise, gene expression data indicated that the ileal mucosal tight-junction-protein expression and innate immune signaling pathways may play a minor role for variation in RFI of pigs in an unchallenged condition [4,5]. However, serum acute-phase-proteins and ileal inflammation markers indicated a stronger immune response in high compared to low RFI pigs [5].…”
Section: Introductionmentioning
confidence: 99%